Hospex: A Historical View and the Need for Change. Issue 3 (1st September 2008) - Cox, CWFM; Roberts, P
Abstract : This article briefly describes the historical background of the Cold War Hospital Exercises from which the necessity for change was identified. The genesis of the current Role 3 Collective Clinical Training is outlined.